The politics of prudence in accounting standards - Georgiou, Omiros (Accounting, organizations and society, 2024)
In the most recent revision of the conceptual framework underlying accounting standards the concept of prudence became the focus of an extraordinary public political dispute. This dispute is explored here by taking an actor-network theory perspective on politics, a ‘dingpolitik’ (Latour, 2005a) or ‘material politics’ (Barry, 2013a), that revolves around things and matters of concern, rather than just interests and ideologies. The analysis unveils how a multiplicity of human actors, including regulators, preparers, auditors, and users of accounts, academics, lawyers, politicians, and journalists, but also material actors such as IASB due process documents and responses, parliamentary debates, official statements, speeches, legal opinions, and financial press articles, come together and raise concerns that are unpredictable and evolving. These concerns ultimately expose the political qualities of prudence that are connected to other controversies relating to other financial reporting issues. At the peak of the political drama that unfolds we see a group of long-term investors commissioning a legal opinion challenging the legality of IFRSs on the grounds that the removal of prudence violates the legal requirement for accounts to show a true and fair view. Both the politics and anti-politics that take place around the concept of prudence lead us to reflect on conceptions of an unrelenting financialisation of accounting standards through fair value accounting and of their (potential) functions in organisations and society.